2022
DOI: 10.1037/neu0000781
|View full text |Cite
|
Sign up to set email alerts
|

Apathy in a high prevalence population of moderate to severe traumatic brain injury: An investigation in Vietnam.

Abstract: Objective: The reduction of goal-directed behavior, termed apathy, is a pervasive and debilitating syndrome after traumatic brain injury (TBI). However, understanding of apathy as a multifaceted construct is limited, especially in Southeast Asian nations. This study aimed to investigate the severity, insight, and psychosocial influences of apathy in executive, emotional, and initiation dimensions in Vietnam-a country with high prevalence of TBI. Method: One hundred and eleven Vietnamese participants (61 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…The demonstrated relationship between apathy, disinhibition and communication found in our study is new but is in line with initial evidence in the literature. Apathy, both after TBI and in healthy people, is recognised to have multiple dimensions including executive, emotional and behavioural apathy (Quang et al, 2022(Quang et al, , 2022b, with all these dimensions potentially affecting communication. Executive apathy is related to the ability to plan and organise thoughts, while emotional apathy refers to emotion expression and social engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated relationship between apathy, disinhibition and communication found in our study is new but is in line with initial evidence in the literature. Apathy, both after TBI and in healthy people, is recognised to have multiple dimensions including executive, emotional and behavioural apathy (Quang et al, 2022(Quang et al, , 2022b, with all these dimensions potentially affecting communication. Executive apathy is related to the ability to plan and organise thoughts, while emotional apathy refers to emotion expression and social engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinical measures that modulate the intensity of intrinsic and extrinsic rewards (e.g., making the task more challenging, increasing the amount of material values earned or increasing levels of praise) may not be successful in increasing motivation after TBI. Instead, methods that support patients’ values, beliefs, and self-esteem, such as motivational interviewing, may be more appropriate (Arnould et al, 2013; Lane-Brown & Tate, 2010; Quang, McDonald, et al, 2022). Given that previous studies are case reports or correlational observations, future clinical trials which comprehensively incorporate motivational interviewing techniques may offer a reliable avenue for effective treatment and management of apathy post TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, although these concepts of extrinsic and intrinsic reward underlying motivation and goal-directed behavior have been extensively utilized in industrial and educational psychology to understand and improve human productivity and goal-directed actions (Benabou & Tirole, 2003; Ryan & Deci, 2020), they have yet to be considered in motivational deficits related to brain disorders. Traumatic brain injury (TBI) is a form of acquired brain injury that commonly affects goal-directed behavior, with up to 72% of people with TBI experiencing apathy (Andersson & Bergedalen, 2002; Andersson et al, 1999; Kant et al, 1998; Lane-Brown & Tate, 2009; Quang, McDonald, et al, 2022). TBI commonly impairs the prefrontal cortex and its connections to subcortical structures which has been demonstrated to associate with clinical apathy and reward processing (Chib et al, 2009; Hogeveen et al, 2021).…”
mentioning
confidence: 99%
“…Considering the established connections between NPS and impairment to the frontal brain network (Robert, 2020), this search was performed utilizing the keyword “frontal contusion” and encompassed hospital admissions recorded from 2016 to 2019, with the patients’ time of injury ranging from 9 to 51 months upon participating in this study. The full recruitment procedure was fully reported in one previous study by Quang, McDonald, et al (2022). Inclusion criteria were: (a) aged from 18 to 65 at the time of the TBI, (b) Glasgow Coma Scale Score <13 (moderate-to-severe coma) administered within 24 hours of injury, (c) brain scan evidence documented by computed tomography.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the recognition that neuropsychiatric symptoms (NPSs) after TBI mainly arise from neuropathology and so should be generalized to cultures other than the West, empirical evidence from Asian populations, including Vietnamese, is very limited. To date, only apathy has been directly examined in Vietnamese individuals with moderate-to-severe TBI (Quang, McDonald et al, 2022). Importantly, initial evidence has suggested that cultural factors, such as family roles and expectations, personal perspectives, and cultural values, may contribute to the way in which NPSs are reported (Quang, Sin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%